CRITICAL SUCCESS FACTORS FOR BROWN-FIELD CAPITAL AND RENEWAL PROJECTS - Warchol, J.; Amadi-Echendu, S.D. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Manufacturing companies operate in a business environment where incremental growth may be achieved through expansion and renewal of existing plant and facilities. Effective management of the critical success factors of such capital development projects may also provide competitive advantage. These projects tend to be of a brown-field nature, characterised by a significant level of risk arising from the interaction between the project implementation and concurrent operation of the existing physical asset base. So it is vital to understand the factors that influence the success of capital expansion and renewal projects in the brown-field context. Although each project has unique features, there are critical success factors that can be customised for successful outcomes in the brown-field environment. This study identifies five critical success factors applicable to brown-field capital expansion and renewal projects. Managerial focus on the critical factors, and the prospects for successful brown-field projects, are discussed in the paper. AFRIKAANSE OPSOMMING: Vervaardigers funksioneer in